Benchmarkingof energy auditfor improving energy efficiencyin Kazakhstan (Journal of Economic Research & Business Administration, 2016)
This article discusses the relationship of benchmarking in the field of energy audits for energy efficiency in the conditions of the Republic of Kazakhstan. It also discusses the methodological aspects of the issue, as well as the possibility of using benchmarking to build an effective system of energy audit.
Keywords: benchmarking; energy audits; energy efficiency; methodology.